The hepatobiliary channels called "accessories": su significación e importancia quirúrgica - Delgado, Bolívar; Aguiar, Alberto; Sbárbaro, Orestes (Cirugía del Uruguay, 2020)
In conjunction with 5 cases of hepatocystic channels, a survey is carried out of the problem posed by the hepato-biliary channels called "accessory". It is poin ted out that such channels are not "accessory", but normal, so far as· their existence is concerned, and abnormal as regards their termination, constituting the only route of biliary drainage of a sector or segment, usually of the hepatic right lobe. Surgical procedures are discussed. In 2 of the 5 cases presented, chaimel ligature was performed, with a subhepatic abscess of biliary origin, as a postoperative complication. In other 2 cases, cholecystectomy was done, leaving the cystic stump wherein the -channel ended. In the remaining case, a channel wound developed, which was sutured and calibrated with Kehr's tube. The course of these patients warrants the contention that in cases of anomalous channels of an appreciable caliber, a conservative approach is in order. Of primary importance is the correct exposure of the pedicular components supplemented, when feasible, by cholangiographic control, befare deciding upon whathatever therapeutic approach.